2004
DOI: 10.1038/sj.bjc.6601731
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibition in the treatment of advanced breast cancer: is there a relationship between potency and clinical efficacy?

Abstract: Two-thirds of breast tumours are oestrogen-receptor positive and 60 -70% of these tumours respond to interventions that reduce the effects of oestrogen. Until recently, tamoxifen was the drug of choice for the treatment of hormone-responsive early and advanced breast cancer. However, tamoxifen is associated with increased incidences of endometrial cancer and thromboembolic disease, and many tumours eventually become resistant to treatment with tamoxifen. Thus, there is a need for alternative therapies with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…In summary, the available evidence does suggest that small differences in oestrogen suppression between the third-generation AIs do not lead to clinically significant differences in overall efficacy as concluded in my review (Sainsbury, 2004). 'The recently presented, but as yet unpublished, results of the Big-Femta (1 -98) study demonstrated similar effects on bone for letrozole in the adjuvant setting.…”
Section: Sirmentioning
confidence: 66%
See 1 more Smart Citation
“…In summary, the available evidence does suggest that small differences in oestrogen suppression between the third-generation AIs do not lead to clinically significant differences in overall efficacy as concluded in my review (Sainsbury, 2004). 'The recently presented, but as yet unpublished, results of the Big-Femta (1 -98) study demonstrated similar effects on bone for letrozole in the adjuvant setting.…”
Section: Sirmentioning
confidence: 66%
“…Firstly, I would like to point out that this claim was not stated in my review (Sainsbury, 2004). Such a statement on the relative efficacy of two agents could only be assessed by direct comparison in a large randomised, double-blind, clinical trial and no such data are available for letrozole and anastrozole.…”
Section: Sirmentioning
confidence: 99%
“…(Sainsbury, 2004), the author claims that differences in the potency of aromatase inhibition and oestrogen suppression among the modern aromatase inhibitors do not translate into differences in efficacy benefits.…”
Section: Sirmentioning
confidence: 99%
“…(Sainsbury 2004). Conversely, a recent randomised comparison of thirdgeneration AI administered for 24 weeks in healthy women showed no significant difference in median percentual change from baseline for plasma concentrations of oestrone (E 1 ), oestradiol (E 2 ) and oestriol (E 3 ; Goss et al 2007).…”
Section: Biochemical Efficacymentioning
confidence: 99%